Acute Negative Allosteric Modulation of M(5) Muscarinic Acetylcholine Receptors Inhibits Oxycodone Self-Administration and Cue-Induced Reactivity with no effect on Antinociception - Gould, Robert W. (ACS Chem Neurosci, 2019)
Opioid Use Disorder (OUD) is a debilitating neuropsychiatric condition characterized by compulsive opioid use, dependence, and repeated relapse after periods of abstinence. Given the high risk of developing OUD following prescription opioid use, the continued need for opioid-induced analgesia, and the limitations of current OUD treatments, it is necessary to develop novel, non-opioid based treatments for OUD and decrease abuse potential of prescription opioids. Recent evidence suggests that negative allosteric modulation (NAM) of the M(5) muscarinic acetylcholine receptor (M(5) mAChR) may provide an alternative therapeutic approach for the treatment of OUD. Previous studies demonstrated localization of M(5) mAChR expression within the mesocorticolimbic reward circuitry and that the selective M(5) NAM ML375 attenuates both cocaine and alcohol self-administration in rats. In the present study, the effects of ML375 were evaluated in rats self-administering the μ-opioid agonists oxycodone or remifentanil on a progressive ratio (PR) schedule or on cue-reactivity (a rodent model of relapse) in the absence of oxycodone following 72 hours of abstinence. ML375 reduced the PR break point for oxycodone and remifentanil self-administration and attenuated cue-elicited responding. Importantly, ML375 did not affect sucrose pellet-maintained responding on a PR schedule or opioid-induced antinociception using the hot-plate and tail-flick assays. We also confirm expression of M(5) mAChR mRNA in the ventral tegmental area and show that this is primarily on dopamine (tyrosine hydroxylase mRNA-positive) neurons. Taken together, these findings suggest that selective functional antagonism of the M(5) mAChR may represent a novel, non-opioid based treatment for OUD.